Octahedral Paclobutrazol–Zinc Complex for Enhanced Chemical Topping Efficacy in Mechanized Cotton Production: A Two-Year Field Evaluation in Xinjiang - Jincheng Shen; Sumei Wan; Guodong Chen; Jianwei Zhang; Chen Liu; Junke Wu; Yong Li; Jie Liu; Shuren Liu; Baojiu Zhang; Meng Lu; Hongqiang Dong (Agronomy, 2025)
Topping is an essential step in cotton cultivation in Xinjiang, China, which can effectively increase the number of bolls per plant and optimize the yield and quality. Paclobutrazol, as a common chemical topping agent for cotton, faces challenges such as unstable topping effect and limited leaf surface absorption during application. In this study, paclobutrazol was used as the ligand and a zinc complex was synthesized by the thermosolvent method to replace paclobutrazol and improve the topping effect on cotton. The structure of the complex was characterized using FTIR, UV-vis, TG, and XRD analyses. The results confirmed that each zinc ion coordinated with four nitrogen atoms from the triazole rings of paclobutrazol and two oxygen atoms from nitrate ions, forming an octahedral geometry. Surface tension measurement and analysis revealed that the complex had a surface tension reduction of 12.75 mN/m compared to paclobutrazol, thereby enhancing the surface activity of the complex in water systems and improving its absorption efficiency on plant leaves. Two-year field trials indicated that the foliar application of the complex at a dosage of 120 g·hm−2 in inhibiting cotton plant height was more stable to that of paclobutrazol or mepiquat chloride. It also shortened the length of fruiting branches, making the shape of cotton plants compact, thereby indirectly improving the ventilation and light penetration of the cotton field and the convenience of mechanical harvesting. Yield data showed that, compared with artificial topping, the complex at a dosage of 120 g·hm−2 treatment increased cotton yield by approximately 4.6%. Therefore, the paclobutrazol–zinc complex is a promising alternative to manual topping and have great application potential in future mechanized cotton production.